COMBATING HUMAN TRAFFICKING IN THE PRESENT INDIAN ERA - Khatker, Rajesh; Bhaira , Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human trafficking is one of the most heinous crimes that undermines the dignity and fundamental rights of individuals. India, due to its socio-economic disparities, porous borders, and complex socio-cultural dynamics, faces significant challenges in eradicating this modern-day form of slavery. This paper explores the prevalence, causes, patterns, and consequences of human trafficking in India. It also provides recommendations for strengthening existing mechanisms to effectively combat human trafficking in the present Indian era.